Phase 1 study of the combination of vemurafenib, carboplatin, and paclitaxel in patients with BRAF‐mutated melanoma and other advanced malignancies. Issue 3 (1st November 2018) - Bhatty, Minny; Kato, Shumei; Piha‐Paul, Sarina A.; Naing, Aung; Subbiah, Vivek; Huang, Helen J.; Karp, Daniel D.; Tsimberidou, Apostolia M.; Zinner, Ralph G.; Hwu, Wen‐Jen; Javle, Milind; Patel, Sapna P.; et al.
Abstract : Background: BRAF inhibitors are effective against selected BRAF V600 ‐mutated tumors. Preclinical data suggest that BRAF inhibition in conjunction with chemotherapy has increased therapeutic activity. Methods: Patients with advanced cancers and BRAF mutations were enrolled into a dose‐escalation study (3+3 design) to determine the maximum tolerated dose (MTD) and dose‐limiting toxicities (DLTs). Results: Nineteen patients with advanced cancers and BRAF mutations were enrolled and received vemurafenib (480‐720 mg orally twice a day), carboplatin (area under the curve [AUC] 5‐6 intravenously every 3 weeks), and paclitaxel (100‐135 mg/m 2 intravenously every 3 weeks). The MTD was not reached, and vemurafenib at 720 mg twice a day, carboplatin at AUC 5, and paclitaxel at 135 mg/m 2 were the last safe dose levels. DLTs included a persistent grade 2 creatinine elevation (n = 1), grade 3 transaminitis (n = 1), and grade 4 thrombocytopenia (n = 1). Non–dose‐limiting toxicities that were grade 3 or higher and occurred in more than 2 patients included grade 3/4 neutropenia (n = 5), grade 3/4 thrombocytopenia (n = 5), grade 3 fatigue (n = 4), and grade 3 anemia (n = 3). Of the 19 patients, 5 (26%; all with melanoma) had a partial response (PR; n = 4) or complete response (CR; n = 1); these responses were mostly durable and lasted 3.1 to 54.1 months. Of the 13 patients previously treated with BRAF and/or mitogen‐activated protein kinase kinase (MEK) inhibitors, 4 (31%) had a CR (n = 1) or PR (n = 3). Patients not treated with prior platinum therapy had a higher response rate than those who did (45% vs 0%; P = .045). Conclusions: The combination of vemurafenib, carboplatin, and paclitaxel is well tolerated and demonstrates encouraging activity, predominantly in patients with advanced melanoma and BRAF V600 mutations, regardless of prior treatment with BRAF and/or MEK inhibitors. Abstract : The combination of vemurafenib, carboplatin, and paclitaxel has demonstrated an acceptable safety profile in patients with advanced cancers and BRAF V600 mutations. In addition, promising signals of anticancer efficacy have been observed in advanced melanoma with BRAF V600 mutations previously treated with BRAF and/or mitogen‐activated protein kinase kinase inhibitors.